What is Hidden by the Perpetual Charity (Articles and Research in Endowment) Book Series (12) Published by the Kuwait Awqaf Public foundation, Kuwait, 2020 CE (مجلة وقف في دراسات الاوقاف, 2026)
The General Purpose of the Scientific Article:The book aims to provide answers to important questions:1. How did endowment projects transform into a soft powerthat managed to establish their position within the generalcivilizational context? This was achieved through the centralWhat is Hidden by the Perpetual Charity(Articles and Research in Endowment)Book Series (12)Published by the Kuwait Awqaf Publicfoundation, Kuwait, 2020 CEPrepared by:Consultant Dr. Tariq bin AbdullahKuwait Awqaf Public foundation, Kuwait71Issue No. EightMUHARM 1445H / JULY 2023AD(Waqf) scientific peer-reviewed journal5. A prevalent practice noted in various documents is theencouragement of fasting during Ramadan by endowers. Thisreflects a religious conviction that highlights the virtuouscompetition of philanthropists in giving and charity during theblessed month Ramadan.6. The documents reveal a wealth of information about individuals,families, scientists, writers, places, terminology, social customs,administrative and financial organizations, and security,providing crucial insight for historians, genealogists, andresearchers interested in the scientific movement in Najd andspecifically Ushaiqer.7. The documents shed light on various tools utilized in Ushaiqer,including measurement tools, currencies, agricultural andirrigation equipment, cooking utensils, offering a glimpse intothe societal lifestyle of that era.8. The documented endowments vary in size (large, medium, small)and type (date palms, houses, machinery), and they underscorethe participation of all segments of society according to theirfinancial capabilities.Concluding Remark on the Research:This research contributes to the revival of the scientific andendowment heritage of Ushaiqer, a town situated northwest ofRiyadh. It served as the primary intellectual center in Najd duringthe 10th-12th centuries AH, laying the scientific groundwork for thesubsequent intellectual revival in the Najd region.